A dual-focused approach to e-commerce product ranking: Leveraging search engine optimization and search engine marketing - Ibrahim, Hassan; Rahmah, Mokhtar; Raza, Muhammad Ahsan; Fauziah, Zainuddin (Elsevier, 2024)
E-commerce platforms and Websites use search engine optimization (SEO) and search engine marketing (SEM) to enhance ranking on search engines. SEO involves improving the website's organic visibility of search engine results. In contrast, SEM is critical in enhancing website visibility through sponsored ads. Product ranking is significant in e-commerce platforms for improving sales, and traditional research is not focused on e-commerce product ranking. This research presents a novel methodology for enhancing product rankings on the Amazon.com platform by combining SEO and SEM strategies. Unlike previous approaches that typically focus on either SEO or SEM in isolation, our method integrates both strategies to address the competitive nature of e-commerce platforms. The novelty of this approach lies in its dual-focus strategy, which harnesses the strengths of both organic and paid search optimizations. Combining the long-term benefits of SEO, which improves organic visibility through content optimizations, with the immediate impact of SEM, which leverages targeted paid advertisements, achieves superior product ranking results. The proposed methodology has been mathematically validated, demonstrating a significant improvement in product rankings from page 5 to page 1 on Amazon’s search results.